Sphagnum palustre clone vs native Pseudoscleropodium purum: A first trial in the field to validate the future of the moss bag technique. (June 2017) - Capozzi, F.; Adamo, P.; Di Palma, A.; Aboal, J.R.; Bargagli, R.; Fernandez, J.A.; Lopez Mahia, P.; Reski, R.; Tretiach, M.; Spagnuolo, V.; Giordano, S.
Abstract: Although a large body of literature exists on the use of transplanted mosses for biomonitoring of air pollution, no article has addressed so far the use and the accumulation performance of a cloned moss for this purpose. In this work, a direct comparison of metal accumulation between bags filled with a Sphagnum palustre L. clone or with native Pseudoscleropodium purum Hedw., one of the most used moss species in biomonitoring surveys, was investigated. The test was performed in sites with different atmospheric contamination levels selected in urban, industrial, agricultural and background areas of Italy and Spain. Among the eighteen elements investigated, S. palustre was significantly enriched in 10 elements (Al, Ba, Cr, Cu, Fe, Hg, Pb, Sr, V and Zn), while P. purum was enriched only in 6 elements (Al, Ba, Cu, Hg, Pb and Sr), and had a consistently lower uptake capacity than S. palustre . The clone proved to be more sensitive in terms of metal uptake and showed a better performance as a bioaccumulator, providing a higher accumulation signal and allowing a finer distinction among the different land uses and levels of pollution. The excellent uptake performance of the S. palustre clone compared to the native P. purum and its low and stable baseline elemental content, evidenced in this work, are key features for the improvement of the moss bag approach and its large scale application. Graphical abstract: Highlights: Metal accumulation was compared between a S. palustre clone and native P. purum . The S. palustre clone proved to be more sensitive in terms of metal uptake. The S. palustre clone showed a higher accumulation signal compared to P. purum . S. palustre allowed a finer distinction among the different levels of pollution. The higher sensitivity of the clone facilitates its use in low impacted environments. Abstract : S. palustre clone shows better uptake ability in terms of accumulation signal and distinction among pollution levels compared to P. purum.